2018
DOI: 10.1016/j.celrep.2018.09.021
|View full text |Cite|
|
Sign up to set email alerts
|

The 10,000 Immunomes Project: Building a Resource for Human Immunology

Abstract: SUMMARY There is increasing appreciation that the immune system plays critical roles not only in the traditional domains of infection and inflammation but also in many areas of biology, including tumorigenesis, metabolism, and even neurobiology. However, one of the major barriers for understanding human immunological mechanisms is that immune assays have not been reproducibly characterized for a sufficiently large and diverse healthy human cohort. Here, we present the 10,000 Immunomes Project (10KIP), a framew… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 59 publications
0
24
0
2
Order By: Relevance
“…As is commonly encountered in flow cytometry studies, comparisons of our data with prior studies are difficult due to varying methodologies and patient populations [24,25]. A recent publication by Zalocusky et.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As is commonly encountered in flow cytometry studies, comparisons of our data with prior studies are difficult due to varying methodologies and patient populations [24,25]. A recent publication by Zalocusky et.…”
Section: Discussionmentioning
confidence: 97%
“…al. undertook a large bioinformatics project to isolate data of healthy normal human subjects from the ImmPort database, and integrate the data for visualization [25]. They were able to capture 10,344 subjects from 83 studies, and normalized and integrated flow cytometry, protein, and gene expression datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Independent prognostic value of six immune-gene signature and clinical parameters Revealing the relationship between prognostic signature and tumor-infiltrating immune cells in TME initiation and progression [25]. Further investigation indicated that the presence of infiltrating immune cells can be used as biomarker for immunotherapy response [26].…”
Section: Validation Of the Predictive Performance Of Immune Prognosismentioning
confidence: 99%
“…Plusieurs Ă©tudes rĂ©centes portant sur le phĂ©notypage gĂ©nĂ©tique et immunologique intĂ©grĂ©s dans des populations saines ont commencĂ© Ă  dĂ©finir les facteurs Ă  l'origine des variations que l'on observe entre rĂ©actions immunitaires des individus [1]. Il s'agit notamment de cohortes Ă©tablies pour rĂ©pondre Ă  des questions similaires Ă  celles posĂ©es dans le cadre de Milieu Intérieur : en particulier, le Human Functional Genomics Project [7], le Human Immunology Project Consortium (HIPC) [8], et le 10K Immunomes [9]. Collectivement, ces Ă©tudes et les premiers rĂ©sultats obtenus dans le cadre de Milieu Intérieur 4 apportent une meilleure dĂ©finition de la variabilitĂ© de la rĂ©ponse immunitaire et des facteurs clĂ©s qui la dĂ©terminent.…”
Section: Resultsunclassified